Practiced Dietary Behaviors and their Predcictive Relation with Health-Related of Fitness Elements t among Upper Elementary School Studentsl (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the practiced dietary behaviors and their predictive relation with health-related elements of physical fitness among the upper elementary school students. The researchers used the descriptive approach with its steps and scientific procedures. The study sample consisted of (200) upper elementary students from the schools of Alqaser Directorate who were chosen randomly, and who underwent special tests related to health fitness elements and filled in a questionnaire about their own dietary behavior .The results of the study showed that there was no predictive relation.between the practiced dietary behaviors and the elements of physical fitness, except for the flexibility element.In the light of the results, the researchers recommended raising nutritional awareness level for school students and improving and enhancing the quality of the  physical education classes related to developing health-related fitness elements.